Calling for a reassessment of rodent diversity in Colombia: description of a new species of Neacomys (Cricetidae: Oryzomyini) from the Magdalena Valley, with a new phylogenetic hypothesis for the genus and comments on its diversification - Colmenares-Pinzón, Javier E. (Zootaxa, 2021)
Neacomys Thomas, 1900 is an oryzomyine genus comprising at least 17 lineages distributed from easternmost Panama to northern Bolivia. As is the case for other groups of the subfamily Sigmodontinae, Neacomys have experienced a substantial increase in the rate of species descriptions in the last two decades, prompted by the progressive generation of morphological, molecular and karyological data. Nevertheless, most of the studies related to the genus have focused on the assessment of Cis-Andean populations, so that the Trans-Andean ones have been relegated to the background. In more than a century, only two species have been described from that region, one of them present in Colombia (N. tenuipes Thomas, 1900). Here, a new species of Neacomys is named and described based on samples collected in montane ecosystems of the Serranía de los Yariguíes, an isolated massif in the Magdalena Valley (Trans-Andean Colombia). Its validity is supported by a unique combination of morphological and molecular characters: Neacomys sp. nov. can be distinguished from other congeners mainly by the presence of broad ochraceous-orange patches on the sides of the muzzle, a gray-based ochraceous buff ventral fur, a thick hamular process of the squamosal, an opened ectotympanic ring, and a narrow anterocone of M1. The species is recovered as a clearly divergent and well-supported monophyletic group in the phylogenies, which implies it is not closely related to any other species in the genus and probably represents an early radiation within it. The new species of Neacomys constitutes the only rodent described from Colombia in more than 50 years and brings the list of mammals of the country to 529 species. Its discovery evidences that Trans-Andean region could be an important source of hidden diversity for the genus, and in Colombia, for rodents in general. Thus, further inventories, especially into remote areas, are needed to unveil this diversity. The fact that the new species seems to be endemic to an isolated mountain range implies it merits attention in terms of conservation.